Analysis of the Impact of the Atmosphere of the Place, Price Perception and Menu Variations on Customer Satisfaction of PT Panca Rasa Nusantara - Austin Alexander Parhusip; Aisyah Azhar Adam (ePaper Bisnis : International Journal of Entrepreneurship and Management, 2024)
This study aims to determine the effect of place atmosphere, price perception and menu variations on consumer satisfaction at PT Panca Rasa Nusantara. This type of research uses quantitative research methods with primary and secondary data sources. The number of samples in this study was 100 respondents who were determined using the Wibisono formula and purposive sampling technique, namely the technique of determining the sample based on certain considerations. This study uses SPSS 25.0 as a data processing tool. The results of this study indicate that partially the atmosphere of the place has no significant effect on consumer satisfaction, while price perceptions and menu variations partially have a positive and significant effect on consumer satisfaction. While simultaneously showing that the atmosphere of the place, perception of prices and menu variations together have a positive and significant effect on consumer satisfaction.